Zonal Disintegration Mechanism of Deep Rock Masses under Coupled High Axial Geostress and Blasting Load - Pu Yuan; Ying Xu (Shock and Vibration, 2018)
Zonal disintegration phenomenon with alternative distribution of fracture zones and nonfracture zones is a characteristic failure in deep rock masses, especially for deep tunnel excavated by drill and blast method. To investigate the mechanism of zonal disintegration under coupled high axial geostress and blasting load, elastic stress field distribution for a circular tunnel in deep isotropic rock masses is obtained. Furthermore, Hoek-Brown criterion is amended by considering blast-induced damage effect. Both radial blasting load and blast-induced damage effect are assumed to decay in a negative exponential function. Taking the deep tunnel of Dingji coal mine in China as engineering background, the number and width of fracture zones are determined by deduced elastic stress field and modified Hoek-Brown criterion. Then numerical computation is conducted. Numerical computation results indicate that both the number and width of fracture zones mainly depend on high axial geostress and mechanical parameters of deep rock masses, and peak radial blasting load plays an important role in determining the width of fracture zone near the excavation.